Análisis de la factibilidad y procesos para la importación de tres tipos de mascarillas de China hacia Ecuador en 2021. - Velasquez Chiliquinga, Juan Francisco (My University, 2021)
The regulations that regulate the importation of medical supplies are composed of a series of standardized processes for the development of commercial activity, therefore prior permits must be obtained from government entities such as SENAE (National Customs Service of Ecuador), INEN ( Ecuadorian Standardization Service), ARCSA (National Agency for Health Regulation, Control and Surveillance) and MSP (Ministry of Public Health). When inquiring about national and international prices on the value of medical supplies that you want to import from China, to observe the importance of comparing prices in the local and international markets will serve to visualize the feasibility of purchasing the selected products. The import process will depend on the negotiation and terms agreed in the international purchase-sale contract, which will specify all the responsibilities of the buyer and the seller, which means and forms of payment, transportation used, among other commercial aspects. The regulatory norms of import processes have different fields such as documentary, procedural, among others; Therefore, SENAE has established a procedure for different types of merchandise that enter Ecuadorian territory.
Las normativas que regulan la importación de insumos médicos están compuestas por una serie de procesos estandarizados para el desarrollo de la actividad comercial, por ende se deberá gestionar los permisos previos a las entidades gubernamentales como SENAE (Servicio Nacional de Aduanas del Ecuador), INEN (Servicio Ecuatoriano de Normalización), ARCSA (Agencia Nacional de Regulación, Control y Vigilancia Sanitaria) y MSP (Ministerio de Salud Pública). Al indagar sobre los precios nacionales e internacionales sobre el valor de los insumos médicos que se desean importar desde China, para observar la importancia de comparar de precios del mercado local e internacional servirá para visualizar la factibilidad de la compra de los productos seleccionados. El proceso de importación dependerá de la negociación y términos acordados en el contrato de compra-venta internacional donde se especificará todas las responsabilidades del comprador y del vendedor, que medios y formas de pago, transporte utilizado entre otros aspectos comerciales. Las normativas regulatorias de los procesos de importación tienen diferentes campos como documentales, procesales entre otros; por lo que la SENAE ha establecido un procedimiento para diferentes tipos de mercancías que ingresen a territorio ecuatoriano.
Keywords: CONTROL ADUANERO; INSUMOS MÉDICOS; IMPORTACIÓN; NORMATIVAS REGULATORIAS